A novel approach to estimate power demand of auxiliary engine loads of light duty vehicles - Gajanayake, Surath; Bandara, Saman; Sugathapala, Thusitha (Frontiers in Mechanical Engineering, 2023)
On par with rapid motorization, excessive energy demand and air pollution have become major challenges in the global context. Fuel economy programs and emission reduction targets have proven to be among the most effective in mitigating these issues. In developing successful fuel economy programs and policies, understanding the factors affecting the fuel consumption of road vehicles is essential. Auxiliary engine loads are one of the commonest factors affecting a vehicle’s fuel economy performance. An auxiliary engine load is defined as the energy utilized to operate auxiliary equipment that draws its power from the vehicle’s engine. This study was limited to light duty vehicles, and an analytical method was adopted to assess the fuel economy impact of the auxiliary equipment in terms of air-conditioning load, alternator load, and water pump and steering pump load. As one of the main deliverables, the study developed a novel approach for estimating and modeling the air-conditioning load which is the major auxiliary energy consumer. For an average car of 100 brake horsepower (bhp) (74.7 kW), the engine auxiliary equipment consumes approximately 13.130 kW of power at an engine operating speed of 3,000 RPM, which amounts to 17.6% of the total bhp output. The major contributors to engine power demand are the air-conditioning unit and the alternator, which account for over 97% of the total auxiliary power requirement, while the water-pump and power steering-pump use relatively little power at 3% of the total auxiliary power demand. The novelty of the method adopted during this study is that it theoretically determines the major contributor of the auxiliary power demand, the air-conditioning load, whereas prior reports have used approaches involving empirical methods.